Penanaman Karakter Religius Melalui Pembiasaan Keagamaan Pada Siswa Di SMK Ma’arif 2 Gombong - Cahyani, Dwi; Wi Hargina, Devi Yaniar (IAINU Kebumen, 2025)
It is undeniable that the existence of the Covid-19 virus a few years ago caused many changes in all parts of life, one of which was the course of character development and improvement in people. Naturally, this shift affects people of all ages, including schoolchildren and vocational students in particular. So that in the world of education is actively reinstilling the values of the main character, religious character as the main foundation for students, the process of cultivating religious character is one of which is carried out with religious habituation activities. The methodology utilized in this study is a subjective methodology with the picked technique, specifically information assortment, meetings, perception and documentation. While information examination utilizes three parts including: information reduction, information display and conclusion. The results of the review demonstrated that strict adjustment completed at SMK Ma'arif 2 Gombong had a positive effect both on understudies and the actual school. A considerable lot of the understudies experienced positive changes, for example, remembering nadhom asmaul husna, ordinary dhuhur supplication in gathering, familiar with performing dhuha petitions, and routine reading surah yasin and tahlil on Fridays. Truth be told, the positive effect got by understudies likewise gives an inspirational perspective for the name of the school too